THE ROLE OF JOB CRAFTING IN THE EFFECT OF PSYCHOLOGICAL SAFETY ON JOB SATISFACTION (Third Sector Social Economic Review, 2023)
Due to the rapidly changing and dynamic environmental factors of the business world, proactive attitudes and behaviors of employees, empowered by a safe and stable environment, have become essential for organizations to survive. Psychological safety climate contributes to the psychological health of employees by increasing the interaction of individuals and workgroups and reducing concerns about the unequal distribution of resources that lead to the exchange or interaction of ideas. Psychological safety climate can provide a working environment that increases the chances of individuals maximizing their returns or minimizing their possible losses and thus increasing their job satisfaction. In the absence of appropriate resources, people lack the motivation to take proactive actions. Based on the job demands-resources theory, this study focuses on the mediating role of job crafting in the effect of psychological safety on job satisfaction. According to the results of the analysis of the data obtained from 397 participants working in companies producing bearings in Ankara, it was seen that psychological safety affects job satisfaction and job crafting in the same direction. Besides, the study showed that job crafting positively affects job satisfaction. Also, the mediating role of job crafting between psychological safety and job satisfaction has been confirmed.
Keywords: Psychological Safety; Job Satisfaction; Job Crafting; Job Demands – Job Resources Theory; Mediation Model